2019
DOI: 10.1021/acs.jpcb.9b04577
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Modulates Membrane Properties and the Interaction of gp41 Fusion Peptide To Promote Membrane Fusion

Abstract: An envelope glycoprotein, gp41, is crucial for the entry of human immunodeficiency virus (HIV) into the host cell. The 20−23 N-terminal amino acid sequence of gp41 plays an important role in promoting fusion between viral and host cells. Interestingly, the structure and function of the fusion peptide are extremely sensitive to the characteristics of the lipid environment. In this present work, we have extensively utilized steady-state and time-resolved fluorescence spectroscopy in tandem with molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…These simplified membranes enable researchers to control target membrane compositions to systematically study the impact of various membrane components on viral fusion. Cholesterol is one membrane component that is of significant interest as it is hypothesized that the cholesterol-rich regions of host membranes facilitate viral fusion peptide engagement, which can promote membrane fusion (9)(10)(11), and vesicle fusion studies have found that cholesterol enhances fusion and pore formation (12)(13)(14). In bulk studies, where fusion between virions and vesicles is observed by fluorescence dequenching and an overall increase in fluorescence signal, cholesterol speeds the rates of IAV lipid mixing (hemifusion) and content mixing (pore formation) (15).…”
Section: Introductionmentioning
confidence: 99%
“…These simplified membranes enable researchers to control target membrane compositions to systematically study the impact of various membrane components on viral fusion. Cholesterol is one membrane component that is of significant interest as it is hypothesized that the cholesterol-rich regions of host membranes facilitate viral fusion peptide engagement, which can promote membrane fusion (9)(10)(11), and vesicle fusion studies have found that cholesterol enhances fusion and pore formation (12)(13)(14). In bulk studies, where fusion between virions and vesicles is observed by fluorescence dequenching and an overall increase in fluorescence signal, cholesterol speeds the rates of IAV lipid mixing (hemifusion) and content mixing (pore formation) (15).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated in bulk studies that cholesterol in target vesicles speeds the rates of IAV hemifusion and fusion pore formation (8), which may be facilitated by the negative spontaneous curvature of cholesterol (9). For other enveloped viruses like human immunodeficiency virus (HIV), fusion peptide insertion is facilitated by cholesterol in the target membrane, which has led to speculation that cholesterol may play some role in facilitating HA engagement for IAV (10)(11)(12). Given that cholesterol may stabilize each fusion intermediate, bulk measurements cannot deconvolve the mechanistic details of cholesterol's influence on IAV fusion.…”
Section: Introductionmentioning
confidence: 99%
“…2 Schematic representation of the fusion reaction profile considering the lipid-stalk model of membrane fusion. The figure has been adapted from reference Meher et al ( 2019b ) with permission …”
Section: Viral Entry Into Host Cellsmentioning
confidence: 99%
“…6 . Initially, gp160 undergoes receptor-mediated proteolytic cleavage into two subunits viz., gp120 (the surface protein) and gp41 (the transmembrane protein) (Meher et al 2019b ; Skehel and Wiley 2000 ; White et al 2008 ). The heterodimer, gp120 and gp41 organize on the viral membrane as a trimer of three gp41 subunits and three gp120 subunit through non-covalent interaction (Berkhout et al 2012 ).…”
Section: Viral Fusion Proteinsmentioning
confidence: 99%